Morphological caste differences in primitively eusocial insects: the Van der Vecht organ of Mischocyttarus paper wasps. (9th June 2020) - de Souza, André Rodrigues; Baptista, Camila Folly; Santos, Eduardo Fernando; da Silva, Rafael Carvalho; da Silva Prato, Amanda; Antonialli-Junior, William; Pereira Soares, Eva Ramona; Barbosa, Bruno Corrêa; do Nascimento, Fábio Santos; Lino-Neto, José
Abstract: Nests of independent-founding primitively eusocial paper wasps are founded by one or a few females. Before worker emergence, foundresses must forage, sometimes leaving the nest unattended. Chemical defence - the application of ant repellent secretions of the Van der Vecht organ (VdVO) on the nest surface - allows brood protection when active defence is weak or not possible. After worker emergence, it is more likely that some wasps stay in the nest, so active nest defence may be more common. Given this constraint on the nest defence, selection for increasing the cuticular secretory area of the VdVO, to improve chemical defence, may be stronger in foundresses (queens) than in workers - morphological castes are hypothesized to evolve. We investigated the occurrence of morphological castes in the Neotropical paper wasp Mischocyttarus . Confirming our prediction, we found that in some (but not all) species, foundresses have a distinct increase in the secretory area of the VdVO in relation to workers; even though there is a strong overlap between caste phenotypes (incipient morphological castes). Implications of these findings for the evolution of morphological castes in primitively eusocial wasps are discussed.